Novel human neurodevelopmental and neurodegenerative disease associated with IRF2BPL gene variants—mechanisms and therapeutic avenues - Bauersachs, Daniel; Bomholtz, Louise; del Rey Mateos, Sara; Kühn, Ralf; Lisowski, Pawel (Frontiers in Neuroscience, 2024)
Recently a broad range of phenotypic abnormalities related to the neurodevelopmental and neurodegenerative disorder NEDAMSS (Neurodevelopmental Disorder with Regression, Abnormal Movements, Loss of Speech, and Seizures) have been associated with rare single-nucleotide polymorphisms (SNPs) or insertion and deletion variants (Indel) in the intron-less gene IRF2BPL. Up to now, 34 patients have been identified through whole exome sequencing carrying different heterozygous pathogenic variants spanning the intron-less gene from the first polyglutamine tract at the N-terminus to the C3HC4 RING domain of the C-terminus of the protein. As a result, the phenotypic spectrum of the patients is highly heterogeneous and ranges from abnormal neurocognitive development to severe neurodegenerative courses with developmental and seizure-related encephalopathies. While the treatment of IRF2BPL-related disorders has focused on alleviating the patient’s symptoms by symptomatic multidisciplinary management, there has been no prospect of entirely relieving the symptoms of the individual patients. Yet, the recent advancement of CRISPR-Cas9-derived gene editing tools, leading to the generation of base editors (BEs) and prime editors (PEs), provide an encouraging new therapeutic avenue for treating NEDAMSS and other neurodevelopmental and neurodegenerative diseases, which contain SNPs or smaller Indels in post-mitotic cell populations of the central nervous system, due to its ability to generate site-specific DNA sequence modifications without creating double-stranded breaks, and recruiting the non-homologous DNA end joining repair mechanism.